The Quality of Risk Disclosure: Evidence from Infrastructure Industry in Indonesia - Geraldina, Ira (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
The objective of this study was to analyze the quality of mandatory and voluntary risk disclosure in Indonesia during the period of 2011 and 2012. The risk disclosure quality is defined as the quality of risk information that are disclosed by firms in term of relative quantity (adjusted by type of sub-industry and firm size), depthness (the potential impact of risk disclosed on firms future performance), the coverage within every type of risk, and the outlook profile of firms risk management. This study used samples of 48 firm-years of infrastructure companies that were listed in Indonesia Stock Exchange. Infrastructure industry was chosen due to the strategic role of this industry to support the acceleration and expansion of Indonesia's economic development. By using a descriptive qualitative method, the result showed that firms were still emphasizing on relative quantity dimension compared to the other three dimensions: coverage, depth, and outlook profile of firm risk management. In addition, the quality of mandatory risk disclosure was better than voluntary risk disclosure either for depth, coverage, or an outlook profile of firm risk management dimension. In other words, financial risk items (mandatory risk disclosure items) have better quality rather than non-financial risk items (voluntary risk disclosure items).